2008
DOI: 10.1152/japplphysiol.00012.2008
|View full text |Cite
|
Sign up to set email alerts
|

Flutamide protects against trauma-hemorrhage-induced liver injury via attenuation of the inflammatory response, oxidative stress, and apopotosis

Abstract: Although studies have shown that administration of testosterone receptor antagonist, flutamide, following trauma-hemorrhage, improves hepatic, cardiovascular, and immune functions, the precise cellular/molecular mechanisms responsible for producing these salutary effects remain largely unknown. To study this, male C3H/HeN mice were subjected to a midline laparotomy and hemorrhagic shock (35+/-5 mmHg for approximately 90 min), followed by resuscitation with Ringer lactate. Flutamide (25 mg/kg) or vehicle was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
2
29
0
1
Order By: Relevance
“…Simultaneous with improvement in cardiac function, RSV treatment resulted in decreased systemic TNF-α level and elevated cardiac ATP content (Figures 3 and 5). An exacerbated proinflammatory response following T-H is well documented (39)(40)(41). Our experiments clearly show improved cardiac function in RSV recipients, although the salutary effect of RSV is likely due to its effect on multiple organs and systemic inflammatory pathways.…”
Section: Discussionsupporting
confidence: 58%
“…Simultaneous with improvement in cardiac function, RSV treatment resulted in decreased systemic TNF-α level and elevated cardiac ATP content (Figures 3 and 5). An exacerbated proinflammatory response following T-H is well documented (39)(40)(41). Our experiments clearly show improved cardiac function in RSV recipients, although the salutary effect of RSV is likely due to its effect on multiple organs and systemic inflammatory pathways.…”
Section: Discussionsupporting
confidence: 58%
“…The impact of gender on mortality and post-injury complications has been debated [29]. Whilst experimental studies indicate superior survival for female subjects, an effect suggested to be linked to female versus male sex steroids, [6][7][8] clinical studies have shown varying findings. Even though several studies have reported that male gender constitutes an independent risk factor for trauma-related mortality other studies have been unable to show this relationship [27,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences among patients surviving severe trauma have been studied both experimentally and in clinical settings. Whilst experimental studies [6][7][8] point to better survival for fertile females, clinical studies have shown somewhat contradictory findings [9][10][11][12][13]. Co-morbidity has been advocated as an important risk factor for post-injury morbidity and mortality but the strength of this association seems to vary depending on injury severity, age and time since admission [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The hypoxic condition following hemorrhage as well as tissue reperfusion following resuscitation are conducive to the production of oxidative damage in most organs (12)(13)(14)(15). Mitochondria is likely to be a major focal point for the generation of reactive oxygen species (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%